Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Select the correct answer.

Which equation is equivalent to the given equation?
[tex]\[ -4(x-5) + 8x = 9x - 3 \][/tex]

A. [tex]\( 5x = 17 \)[/tex]

B. [tex]\(-5x = -23\)[/tex]

C. [tex]\(5x = -12\)[/tex]

D. [tex]\(-5x = 2\)[/tex]


Sagot :

Certainly! Let's solve the given equation step-by-step to find an equivalent equation.

The given equation is:

[tex]\[ -4(x - 5) + 8x = 9x - 3 \][/tex]

1. First, distribute -4 to the terms inside the parentheses:

[tex]\[ -4 \cdot (x - 5) = -4x + 20 \][/tex]

So, the equation now becomes:

[tex]\[ -4x + 20 + 8x = 9x - 3 \][/tex]

2. Next, combine the like terms on the left-hand side:

[tex]\[ -4x + 8x = 4x \][/tex]

So, the equation simplifies to:

[tex]\[ 4x + 20 = 9x - 3 \][/tex]

3. Subtract 9x from both sides to move all terms involving [tex]\( x \)[/tex] to one side:

[tex]\[ 4x - 9x + 20 = -3 \][/tex]

This simplifies to:

[tex]\[ -5x + 20 = -3 \][/tex]

4. Subtract 20 from both sides to isolate the term involving [tex]\( x \)[/tex] on one side:

[tex]\[ -5x = -3 - 20 \][/tex]

Which simplifies to:

[tex]\[ -5x = -23 \][/tex]

So, the equation that is equivalent to the given equation is:

[tex]\[ -5x = -23 \][/tex]

Hence, the correct answer is:

B. [tex]\( -5x = -23 \)[/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.